Electrophysiological audiograms in seven beluga whales (Delphinapterus leucas) from the Okhotsk Sea population - Sysueva, Evgeniya V.; Nechaev, Dmitry I.; Popov, Vladimir V.; Supin, Alexander Ya (Proceedings of Meetings on Acoustics, 2018)
Hearing thresholds were measured and audiograms were obtained in seven belugas, two males and five females, provisionally 2 to 8 years old. The measurements were performed using a transducer located 1 m in front of the head. The stimuli were tone pip trains of carrier frequencies ranging from 11.2 to 128 kHz with a pip rate of 1 kHz. Auditory evoked potentials (the rate following responses) were recorded from the head vertex. In majority of the subjects, audiograms were similar to the typical odontocete audiograms with the lowest thresholds (53.4±2.3 dB re 1 μPa) at mid-frequency range (from 32 to 76 kHz) and a threshold increase (up to 73.8±4.9 dB re 1 μPa) at high frequencies (90-128 kHz). One beluga (female, 6-7 years old) featured an asymmetric hearing loss within a frequency range from 22.5 to 54 kHz. The reason for the loss is the subject for not defined. The evoked potential audiograms should be included into base screening of odontocete subjects involved in any kind of hearing research.